Antibacterial effect of Leucocyte and Platelet Rich-Fibrin against Klebsiella pneumoniae and Staphylococcus aureus – A pilot study - Mendes, Ana Francisca; Coelho, Cristina; Mendes, Inês; Silva, Laura; Melo-Ferraz, António; Begoña Criado, Maria; Monteiro, Maria do Céu; Miller, Paulo (Scientific Letters, 2024)
Leukocyte and platelet-rich fibrin (L-PRF) is a platelet concentrate used in diverse areas of tissue healing and regeneration. Thus, its antibacterial properties are promising. In this study, we evaluated the antibacterial effect of L-PRF, in its exudate and membrane forms, against oral cavity opportunistic bacteria Klebsiella pneumoniae and Staphylococcus aureus. Blood samples were collected from three healthy donors. Blood was centrifuged at 2,700 rpm for 12 minutes. This resulted in an L-PRF membrane, and then, from its compression, an L-PRF exudate. These two forms of L-PRF were placed on Mueller-Hinton Agar previously inoculated with the bacteria. The L-PRF membrane was placed directly into the culture medium, and the L-PRF exudate was impregnated in different quantities onto paper disks (Oxoid). The membrane inhibition values varied between 11 and 13 mm for K. pneumoniae and 13 mm for S. aureus. For the L-PRF exudate, inhibition only occurred for quantities of 5 and 20 μL of exudate in the case of K. pneumoniae and for 20 μL of exudate in the case of S. aureus. Thus, L-PRF products effectively inhibit bacterial growth, particularly opportunistic bacteria, such as K. pneumoniae and S. aureus.